Optimizing hypertension management in China: care cascade insights and individual determinants from a national survey - Yu, Yiwen; He, Liu; Feng, Zixuan; Shi, Zhenyu; Cao, Zhong; Chen, Qiushi; Geldsetzer, Pascal; Bärnighausen, Till; He, Ping; Yang, Ting; Chen, Simiao; Wang, Chen (Current medical research and opinion, 2025)
Hypertension is common in China, and its prevalence has been increasing. However, it remains inadequately controlled. This study examined patterns of patient attrition across the stages of hypertension management in the general population and their variations across subpopulations, and assessed the role of individual-level determinants of hypertension management. The findings would help inform clinical practice and policy decisions to enhance hypertension management in China. Using data from the 2015 China Health and Nutrition Survey among adults aged ≥18 years, we applied the framework of care cascade to hypertension management and defined three cascade stages: (1) diagnosed, (2) treated, and (3) controlled. The outcomes were based on blood pressure measurements and self-reports. Associations between cascade progression and individual characteristics were assessed using a multivariable modified Poisson regression with community fixed effects. Among 3,214 hypertensive patients, 45.1% (95% confidence interval [CI]: 43.4-46.8) were diagnosed, 38.5% (36.8-40.2) received treatment, and only 13.8% (12.6-15.0) achieved blood pressure control. The proportion of undiagnosed individuals was markedly higher among the younger adults, with 82.6% (79.0-86.2) of those <45 years old and 92.6% (88.1-97.2) of those <35 years old remaining undiagnosed. Compared with those with a healthy weight, the underweight individuals were less likely to be diagnosed, with a relative risk (RR) of 0.66 (95% CI: 0.44-0.99, p = 0.044). By contrast, the obese patients were more likely to be diagnosed (RR [95% CI]:1.29 [1.16-1.45], p < 0.001), but less likely to achieve blood pressure control (RR [95% CI]: 0.58 [0.45-0.76], p < 0.001). In rural and economically underdeveloped areas, insured patients were less likely to achieve blood pressure control than uninsured patients. Our study results confirm that hypertension remains a major public health challenge in China, with its high prevalence and persistently low diagnosis, treatment, and control rates, both in the general population and across diverse demographic and socioeconomic subgroups. To address this burden, China should pay greater attention to young hypertensive adults by supporting their screening and early diagnosis. In addition, efforts should be made to strengthen therapeutic concordance among all hypertensive patients and to implement public health measures that promote healthy diets and physical activity, particularly among overweight and obese individuals. Expanding access to a broader range of antihypertensive medications, including novel agents, will also be essential for improving blood pressure control nationwide.